2004
DOI: 10.1002/chin.200447248
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Biological Activity and Synthesis of Drimane Sesquiterpenoids

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(55 citation statements)
references
References 2 publications
2
52
0
1
Order By: Relevance
“…Compared with polygodial, the n-hexane extract emerged as the best antifeedant alternative since the wide variety of terpenes present in this extract could involve synergisms, which would also reduce and delay aphid resistance and habituation under continuous exposure for a long time (Isman 2002). Additionally, the persistence and phytotoxicity under field conditions should be studied, since it has been suggested that some drimanes can interfere in plant growth (Hardie et al 1992;Jansen and Groot 2004). Notably, we did not detect any phytotoxic effects of these compounds during the experimentation period.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Compared with polygodial, the n-hexane extract emerged as the best antifeedant alternative since the wide variety of terpenes present in this extract could involve synergisms, which would also reduce and delay aphid resistance and habituation under continuous exposure for a long time (Isman 2002). Additionally, the persistence and phytotoxicity under field conditions should be studied, since it has been suggested that some drimanes can interfere in plant growth (Hardie et al 1992;Jansen and Groot 2004). Notably, we did not detect any phytotoxic effects of these compounds during the experimentation period.…”
Section: Discussionmentioning
confidence: 71%
“…Previous chemical fractionation of this extract revealed the presence of four drimanes, with polygodial being the most abundant (Rodríguez et al 2005). Antifeedant activity of polygodial and other related drimane-type compounds is also well documented (Jansen and Groot 2004). Previous results have shown that polygodial is a potent antifeedant for some Lepidoptera larvae (Blaney et al 1987;Messchendorp et al 2000;Zapata et al 2009) and Coleoptera beetles (Gols et al 1996).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…(Polygonaceae) have been thoroughly researched owing to their strong antifeedant activities and considerable attention has been devoted to the synthesis of these compounds. 401 The reactivity of the unsaturated dialdehyde functionality towards biological nucleophiles is considered to account for the antifeedant activity of these substances. 401 The antifeedant activity of polygodial acetal derivatives (propylene and ethylene) is consistent with the proposed adduct formation with amino groups.…”
Section: Sesquiterpenesmentioning
confidence: 99%
“…More recently, the drimane sesquiterpenes occurring in plants, fungi and some marine organisms have found special attention in defensive responses. 115 So far, very little is known on the production of volatile terpenes in plant roots as indirect defensive compounds against nematodes and other plant herbivores. However, one can expect a function similar to that in leaf tissues.…”
Section: Function Of Terpenes In Plant Defencementioning
confidence: 99%